Investigations into speech intelligibility in the presence of different masking noises for hearing aids with variable attack and release times - Hojan, E.; Fastl, H.; Malenda, J.; Hojan-Jezierska, D. (Archives of Acoustics, 2005)
People with hearing impairments experience a reduction in speech intelligibility in noisy surroundings. The extent of this reduction depends on the degree of impairment in the temporal resolution of the patient's ear, too. The change of the speech intelligibility of hearing-impaired people was investigated in the presence of different masking noises, especially when using hearing aids with adjustable attack (AT) and release (RT) times within same frequency bands. Key words: speech intelligibility, masking noises, hearing aids, attack and release times.